Effect of Covid-19 pandemic induced lockdown on sleep wake pattern and personal well-being of undergraduate medical students of West Bengal - Biswas, Sujata; Saha, Bhaskar; Halder, Indranil; Basu, Gandhari; Ghosh, Anupam (Asian Journal of Medical Sciences, 2021)
Background: COVID-19 pandemic induced lockdown and the social restrictions had a profound impact on the circadian rhythm driven sleep-wake schedule of the home confined population.Aims and Objective: Our study explored the effect of COVID-19 pandemic induced lockdown on sleep wake pattern and personal well-being of medical students of West BengalMaterials and Methods: An observational, questionnaire-based online survey was conducted using the URL linked Google form. The online survey was conducted through social media platforms as per CHERRIES checklist guideline. Information on demographic profile, before and after lockdown sleep-wake pattern, social wellbeing and general lifestyle was obtained. Any student with any sleeping disorder or on drugs was excluded. Mean (SE), median, range, proportion was calculated as per attributes. Fisher’s exact chi square test and paired t test was done to test association and to compare means of the attributes.Results: The mean age of students was 20.26 years. The average daily time spent on electronic media got doubled during lockdown. Sleep disorder was reported by 53.0% male and 47.0% students. More than half of respondents reported increased napping during daytime, irregular timing for meal intake and low mood. Anxiety was present in every two out of three participants. Females gained more weight during lockdown. The gender difference in sleep duration became significant. Lockdown effect on the average daily media time was significant. The sleep disturbance at night and physical inactivity was significantly more among female students.Conclusion: COVID-19 lockdown leads to delayed sleep-wake cycle, irregular meal timings and excessive digital exposure among medical students with gender based differential impact.